The wolf's chicken stew - Kasza, Keiko (New York : Scholastic, 1987)
The wolf loves to eat more than anything in the world and one day he has a terrible craving for chicken stew. He spots a chicken who seems just right, but then he thinks how much more stew there will be if he fattens her up before dining himself. So he goes home and begins to cook all kinds of scrumptious food for the chicken to eat. A big surprise is in store for the wolf when he finally visits Mrs. Chicken to collect his meal.